Use of Manipulative Media as A Stimulation Of Ability To Understand The Concept of Early Children's Age - Agustina Nur Palupi (Department of Early childhood Education, 2020)
Every child has the right and needs for stimulation of his development. One of them is cognitive. Aspects of cognitive development can be stimulated through mathematics learning. But children can find it difficult to understand mathematical concepts because reasoning and logic are needed, whereas mathematical concepts are not concrete. For this reason, concrete media need to be used to demonstrate or illustrate the concept, the media are manipulative. The purpose of this study is to analyze articles and documents resulting from research on the use of manipulative media as a stimulation of the ability to recognize the concept of child numbers. Method: This research uses a literature review method. There are criteria in searching journals so that 20 journals are found to be analyzed based on population, sample, variables, data analysis, type of research design, and research results. Results and discussion: Literature review shows that the use of manipulative media in early childhood education varies greatly in terms of media material, its play, and its effectiveness. The manipulative media in question such as grain media, number blocks, clock puzzles, container marbles, picture cards, congklak numbers cards, numbers fishing games, and others. While the ability to recognize the concept of numbers in question such as the meaning of the symbol number of concepts a lot a little, counting, and others. Statistical analysis shows the application of manipulative media can stimulate the ability to recognize the concept of numbers in children, increase the activities of children and teachers, and found the response of children who are happy with the use of manipulative media. Conclusion: Manipulative media can stimulate the ability to recognize the concept of child numbers.